2023
DOI: 10.3390/molecules28073191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of High Specific Surface Lithium-Ion Sieve Templated by Bacterial Cellulose for Selective Adsorption of Li+

Abstract: In recent years, with the development of batteries, ceramics, glass and other industries, the demand for lithium has increased rapidly. Due to the rich lithium resources in seawater and salt-lake brine, the question of how to selectively adsorb and separate lithium ions from such brine has attracted the attention and research of many scholars. The Li-ion sieve stands out from other methods thanks to its excellent special adsorption and separation performance. In this paper, mesoporous titanium dioxide and lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…By contrast, Qian et al [69] applied a multi-step crosslinking strategy to afford multiple adsorption binding sites, as well as to enhance the mechanical stability of the produced granules. Zhang et al [70] reported the preparation of high-specific surface LISs templated by bacterial CLS for the selective adsorption of Li ions. The templated LISs were synthesized as follows: Bacterial CLS (B-CLS) hydrogel was added to deionized water for 15 min to enhance swelling, followed by freezing with liquid nitrogen and freeze-drying to obtain a B-CLS aerogel network structure.…”
Section: Metal-based Liss Granulated With Cellulosementioning
confidence: 99%
“…By contrast, Qian et al [69] applied a multi-step crosslinking strategy to afford multiple adsorption binding sites, as well as to enhance the mechanical stability of the produced granules. Zhang et al [70] reported the preparation of high-specific surface LISs templated by bacterial CLS for the selective adsorption of Li ions. The templated LISs were synthesized as follows: Bacterial CLS (B-CLS) hydrogel was added to deionized water for 15 min to enhance swelling, followed by freezing with liquid nitrogen and freeze-drying to obtain a B-CLS aerogel network structure.…”
Section: Metal-based Liss Granulated With Cellulosementioning
confidence: 99%
“…Contrary to several reports on the use of organic and inorganic materials as binders for the granulation of metal-based LISs, reports on the use of biopolymers as binders are limited in the open literature (cf. Figure 4) [24,[49][50][51][52][53][54][71][72][73][74][75][76][77][78][79]. Additionally, there are currently no review articles that highlight the available knowledge gaps on the use of biopolymers as binders for the granulation of LISs.…”
Section: Granulation Of Liss Using Inorganic Materialsmentioning
confidence: 99%
“…Additionally, there are currently no review articles that highlight the available knowledge gaps on the use of biopolymers as binders for the granulation of LISs. Most recent studies have focused on the use of chitosan, alginate, agar, and cellulose as binders to prepare granulated LISs [24,[49][50][51][52][53][54][71][72][73][74][75][76][77][78][79]. For instance, numerous studies [49][50][51][52][53] have reported on the use of chitosan in various forms (cross-linked and non-cross-linked) as binder for the granulation of LISs.…”
Section: Granulation Of Liss Using Inorganic Materialsmentioning
confidence: 99%
See 2 more Smart Citations